Learning to Live with a Chronic Rheumatic Disease - Sá, C.; Oliveira, A. (People Being Patients: International, Interdisciplinary Perspectives, 2014)
(Nota: o livro tem data de publicação de 2013 mas só foi efectivamente publicado em 2014) ... A chronic illness can be viewed as a challenge to the patient, demanding new learning and adaptation to different habits and ways of living. A rheumatic disease, at any stage, always affects the person at a psychological, social, spiritual and emotional level. The way a patient reacts to a chronic illness varies and may depend on his emotional condition. With the progressive development of a rheumatic disease there arise increasingly severe limitations affecting the patient’s life. Consequently, the hope for a better condition often fades away in time, giving way to despair. At a certain moment, patients, family members and even caregivers, are confronted with the impossibility of healing. Sometimes is even very difficult to find a good way to relieve suffering or provide better health conditions to the patients. It is vital to help patients to accept their situation and to adapt to the limitations and disabilities derived from a rheumatic disease, encouraging their autonomy, emotional balance and self-care. If they feel confident in treatments and health care, they are more motivated to finding new objectives in their lives, knowing is always possible to improve in some aspect. Here we aim to understand the perceptions of patients with a rheumatic disease of their own illness and perspectives in life. We developed a focus-group with eleven patients to address several topics, such as their expectations on the future, the way they adapted to a chronic disease and what they would like to change in their lives. The participants revealed that they are frequently aware of the need to make changes in their lives, adapting to the life events in which they are involved, and discovering their rights and duties in each circumstance. In general, despite their illness, doubts and fears, they do not wish to be a burden to anyone. So, they show some confidence in the future, discovering their capacities to deal with their health problems.